RADIOCAPACITY MODEL APPLIANCE FOR ECOLOGICAL STANDARDIZATION OF RADIATION FACTOR IN A LAKE ECOSYSTEM - Matveeva, Iryna (Proceedings of National Aviation University (archive), 2014)
In the article a new approach to creation of an ecological standardization system is offered. Such system does not coincide with the working hygienic standardization system. Basing on the radiation capacity model and theory of ecosystems reliability a method of defining of critical biota condition on an example of a lake ecosystem is offered. Through an estimation and control of a critical radiation dose on the given biota, through radiocapacity models the levels of permissible radionuclides pollution of the ecosystem’s components are determined. The levels of permissible radionuclides pollution are estimated as such, at which radiation dose on the critical biota of the lake may not exceed the allowed limit — 4 Gy/year